Robert Bartlett (1875-1946) - Stewart, Hugh (ARCTIC, 1986)
Although he was indisputably one of the world's greatest arctic mariners, Captain Robert A. Barlett's name and accomplishments are relatively obscure. As a sealer, arctic explorer, ice captain, and scientist, Bartlett made over 40 voyages in more than half a century at sea. He was decorated by the American Congress, the Explorers' Club, and geographical societies on two continents. He survived two shipwrecks and, thanks to his skill and perseverance, prevented a number of others, and he saved the lives of many shipmates. An eccentric who could play Chopin records as his ship was about to sink below the arctic ice, a man frequently inconsistent in accounts of his own voyages, a man blessed with incredible good luck when at sea, a known drinker who professed to be a teetotaler, Bartlett was, nevertheless, an exceptional leader of men. . From the perspective of the late twentieth century, three periods loom pre-eminent in Bartlett's life. The first was the decade between 1898 and 1908 during which he accompanied Robert Peary on three separate attempts to reach the North Pole, the second was his captaincy of the Karluk on the Canadian Arctic Expedition in 1913 and 1914, and the third, his scientific voyages on the Morrissey from 1925 to 1945. Robert Peary encountered Bartlett in 1898 when Bartlett was the first mate on the Windward, the flagship of Peary's first unsuccessful journey to the North Pole. On Peary's subsequent expeditions Bartlett played critical roles. . Yet Peary denied Bartlett a part in the final dash for the Pole and reserved this privilege for himself. . The Karluk, under Bartlett's captaincy, was to be the main vessel in the Canadian Arctic Expedition of 1913. The expedition to the Western Arctic is famous for the anthropological and geographical work conducted by Vilhjalmur Stefansson and Diamond Jenness; however, the real hero of the venture has surely to be Robert Bartlett. When Stefansson left the Karluk in September 1913, ostensibly for a brief hunting foray on the mainland, she had been ...